ANALYSIS OF ETHICAL CLIMATE, SPIRITUALITY IN THE WORKPLACE, AND ORGANIZATIONAL COMMITMENT TO DEVIANT BEHAVIOR OF ASN BLITAR REGENCY GOVERNMENT - Yuriasari*, Indari; Arisyahidin, Arisyahidin; Talkah, Abu; Askafi, Eka (Jurnal Apresiasi Ekonomi, 2024)
This research aims at examining and analyzing: (1) the effect of ethical climate on deviant behavior; (2) the effect of workplace spirituality on deviant behavior; (3) the effect of organizational commitment on deviant behavior; (4) the effect of ethical climate on workplace spirituality; (5) the effect of ethical climate on organizational commitment; (6) the effect of ethical climate on deviant behavior mediated by workplace spirituality; (7) the effect of ethical climate on deviant behavior mediated by organizational commitment. This research using quantitative study with SmartPLS analysis methode, and the population is 207 people of the regional unit apparatus holding the structural positions of echelon 2b, 3a, and 3b in Blitar Regency Government, and 67 of them are taken as the samples. The results of the study show that ethical climate does not influence deviant behavior, but workplace spirituality affects deviant behavior. Meanwhile, organizational commitment does not affect deviant behavior, but ethical climate affects organizational commitment. In addition, ethical climate influences workplace spirituality, also the organizational commitment. Furthermore, the results of the study also reveal that the ethical climate influences deviant behavior mediated by workplace spirituality, but not through organizational commitment.  Keywords: Ethical Climate, Workplace Spirituality, Organizational Commitment, Deviant Behavior